NEED ANALYSIS OF USING GOOGLE FORM FOR LEARNING - Herlina Herlina; Acim Acim; Misnah Misnah; Rifka Khairunnisa (Jurnal Dikdas, 2019)
Industrial era 4.0 not only has implications for the industrial world, but also has a real impact on the implementation of learning in the classroom. The use of Information Technology (IT) is common. Prohibit students from using an Android-based device (gadget) in the lecture room to agree on a way out. This paper is the result of preliminary research conducted on Information Technology-based learning by utilizing Google applications compiled by Google. The purpose of this study is the distance learning needed by Google. This study uses qualitative considerations through interviews, observations and questionnaires. The results showed that google forms are needed by students because of the lecturers, lecture policies, accessibility and the students themselves.